Baicalin against obesity and insulin resistance through activation of AKT/AS160/GLUT4 pathway. (15th June 2017) - Fang, Penghua; Yu, Mei; Zhang, Lei; Wan, Dan; Shi, Mingyi; Zhu, Yan; Bo, Ping; Zhang, Zhenwen
Abstract: Obesity may cause several metabolic complications, including insulin resistance and type 2 diabetes mellitus. Despite great advances in medicine, people still keep exploring novel and effective drugs for treatment of obesity and insulin resistance. The aim of this study was to survey if baicalin might ameliorate obesity-induced insulin resistance and to explore its signal mechanisms in skeletal muscles of mice. Diet-induced obese (DIO) mice were given 50 mg/kg baicalin intraperitoneally (i.p.) once a day for 21 days, and C2C12 myotubes were treated with 100, 200, 400 μM baicalin for 12 h in this study. Then insulin resistance indexes and insulin signal protein levels in skeletal muscles were examined. We discovered that administration of baicalin decreased food intake, body weight, HOMA-IR and NT-PGC-1α levels, but enhanced GLUT4, PGC-1α, pP38MAPK, pAKT and pAS160 contents, as well as GLUT4 mRNA, PGC-1α mRNA, PPARγ mRNA, GLUT1 mRNA expression in skeletal muscles of obese mice and myotubes of C2C12 cells, and reversed high fat diet-induced glucose and insulin intolerance, hyperglycemia and insulin resistance in the mice. These results suggest that baicalin is a powerful and promising agent for treatment of obesity and insulin resistance via Akt/AS160/GLUT4 and P38MAPK/PGC1α/GLUT4 pathway. Highlights: I.p injection of baicalin decreases body weight and food intake of obese mice. I.p injection of baicalin reduces blood glucose concentration and insulin resistance. I.p injection of baicalin increases GLUT4 expression levels in skeletal muscle. I.p injection of baicalin improves GLUT4 translocation level in skeletal muscle. Baicalin attenuates skeletal muscle insulin resistance via the Akt/AS160/GLUT4 pathway.